Pengaruh Organisasi Terhadap Prestasi Akademik Mahasiswa Di UIN KH. Achmad Siddiq Jember - Sofyan, Muhammad; Iskandar, Robby Sofyan; Farhan, Rifki Dwi; Zuhro’ Fitriana, Ani Qotuz (CV. ITTC INDONESIA, 2023)
According to Prof. Dr. sondang P. Siagian, organization is a form of association between two or more people who work together and are formally bound in the framework of achieving predetermined goals and in that bond there is a person or group of people called subordinates. The student organization referred to in this study is a forum or facility for its members as students to add insight into knowledge both from an academic and social perspective so that it can help improve their academic achievement and ability to socialize in society. This research itself is related to extra-student activities where students should be aware that the majors student association is an organization that is under the auspices of the department where they carry out lecture activities, therefore a department-level student organization should not have a negative impact on student academic activities as its members. , on the contrary, this student organization should have a positive impact on academic activities and student achievement as its members. The organization a student participates in can also shape the character of a student in it. However, students who join these organizations must also consider or maintain the academic value of their studies. Don't put the organization first and don't care about the value of academic achievement. It can be concluded that most students who take part in this organization at Uin Khas Jember, when they enter the organizatio they will be more concerned with the organization and have a negative impact on their academic achievement scores.